2005
DOI: 10.1038/nn1514
|View full text |Cite
|
Sign up to set email alerts
|

Regret and its avoidance: a neuroimaging study of choice behavior

Abstract: Human decisions can be shaped by predictions of emotions that ensue after choosing advantageously or disadvantageously. Indeed, anticipating regret is a powerful predictor of future choices. We measured brain activity using functional magnetic resonance imaging (fMRI) while subjects selected between two gambles wherein regret was induced by providing information about the outcome of the unchosen gamble. Increasing regret enhanced activity in the medial orbitofrontal region, the anterior cingulate cortex and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
565
4
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 570 publications
(617 citation statements)
references
References 46 publications
41
565
4
7
Order By: Relevance
“…Camille et al (2004) and Coricelli et al (2005), using the same experimental paradigm in an fMRI study, show that the orbitofrontal cortex has a fundamental role in experiencing regret and integrating cognitive and emotional components of the entire process of decision-making. Across repetition of this task, participants tend to become regret aversive.…”
Section: Testing the Regret Explanation Of Allaisian Behaviourmentioning
confidence: 96%
“…Camille et al (2004) and Coricelli et al (2005), using the same experimental paradigm in an fMRI study, show that the orbitofrontal cortex has a fundamental role in experiencing regret and integrating cognitive and emotional components of the entire process of decision-making. Across repetition of this task, participants tend to become regret aversive.…”
Section: Testing the Regret Explanation Of Allaisian Behaviourmentioning
confidence: 96%
“…The other areas associated with regret but not with rejoice included the right angular gyrus, left superior frontal cortex, and the medial orbitofrontal cortex. In a previous study of regret using monetary outcomes, the medial orbitofrontal cortex was implicated in the experience of regret (Coricelli et al, 2005). This study also found that the presence of regret activated the inferior parietal lobule, a region that partially overlapped the area of regret-related activity we observed in the angular gyrus.…”
Section: Regret and Rejoicingsupporting
confidence: 81%
“…A few neuroeconomic studies have investigated the neural correlates of regret when payoffs are monetary (Coricelli et al, 2005;Lohrenz, McCabe, Camerer, & Montague, 2007). These studies find that activity in the medial orbitofrontal cortex (OFC), anterior cingulate cortex (ACC), and right hippocampus is positively correlated with the magnitude of financial regret.…”
Section: Regret and Rejoicingmentioning
confidence: 99%
See 1 more Smart Citation
“…There is much empirical evidence for this behavioural premise. Take for example Coricelli et al (2005) who, using neuroimaging techniques, show that the area of the human brain that is active when decision-makers experience regret after having made a (poor) choice, is also highly active split seconds before they make a choice. In their words "anticipating regret is a powerful predictor of future choices".…”
Section: Introductionmentioning
confidence: 99%